The state of the art of planning and planning education in Australia and New Zealand. - Freestone, Robert; Goodman, Robin; Burton, Paul (Routledge, 2018)
Future needs and challenges, the respective contributions of practice and research, and the state of education are constant preoccupations of the planning profession. These issues are regularly canvassed in academic and professional forums. This paper provides an Australasian (Australia and New Zealand) perspective in reporting the findings from an online survey of over 250 planners and planning academics from this part of the world. The survey was inspired by the work of Klaus Kunzmann and Martina Koll-Schretzenmayr who have conducted two major state of the art surveys in Europe and Asia since 2014. There are three main foci. The first is how academic and professional planners define the major challenges for the planning profession and the productiveness of their engagement. The second is knowledge exchange across the academic research / practitioner divide in enhancing the profile and contributions of the profession generally through constructive dialogue. The third is an assessment of the present state of and future needs for planning education. This professional self-assessment yields overall positive results amid guardedness and caution. There is common ground with the European and Asian surveys albeit falling short of the same sense of grimness and crisis moving forward.
Keywords: Stadtentwicklungsplanung; Stadtplanung; Raumplanung; Planungssystem; Planungspraxis; Planungstheorie; Planerausbildung; Internationaler Vergleich; Überblick